Controllably Alloyed, Low Density, Free-standing Ni-Co and Ni-Graphene Sponges for Electrocatalytic Water Splitting - Vineesh, Thazhe Veettil; Mubarak, Suhail; Hahm, Myung Gwan; Prabu, V.; Alwarappan, Subbiah; Narayanan, Tharangattu N. (Scientific reports, 2016)
Synthesis of low cost, durable and efficient electrocatalysts that support oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) are the bottlenecks in water electrolysis. Here we propose a strategy for the development of controllably alloyed, porous, and low density nickel (Ni) and cobalt (Co) based alloys - whose electrocatalytic properties can be tuned to make them multifunctional. Ni and Co based alloy with the chemical structure of Ni 1 Co 2 is identified as an efficient OER catalyst among other stoichiometric structures in terms of over potential @ 10 mAcm −2 (1.629 V), stability, low tafel slope (87.3 mV/dec), and high Faradaic efficiency (92%), and its OER performance is also found to be on par with the benchmarked IrO 2 . Tunability in the porous metal synthesis strategy allowed the incorporation of graphene during the Ni sponge formation, and the Ni- incorporated nitrogen doped graphene sponge (Ni-NG) is found to have very high HER activity. A water electrolysis cell fabricated and demonstrated with these freestanding electrodes is found to have high stability (>10 hours) and large current density (10 mAcm −2 @ 1.6 V), opening new avenues in the design and development of cost effective and light weight energy devices.